Why Wait Until They Commit a Crime? : Moral Imbecility and the Problem of Knowledge in Progressive America, 1880-1920 - Chamberlain, Chelsea D (2015)
Focusing on the forty-year period from 1880 to 1920, this thesis explores moral imbecility--the lack of a moral sense at birth--as a contested medical diagnosis that embodied many of modernizing America's greatest fears. It argues that moral imbecility played a pivotal role in facilitating the emergence of several hallmarks of modern America. The diagnosis legitimated medical experts’ far-reaching cultural authority, encouraged the rise of a surveillance society, and secured the growth of a medicalized bureaucratic state responsible for institutionalizing hundreds of thousands of people. As a potent medico-cultural threat based upon new and disputed knowledge claims, it became an important battleground on which various groups struggled over the bounds of professional knowledge and the use of that knowledge in solving the problems of modern America. Physicians, psychologists, educators, legal professionals, and members of the public wrestled over how to define, identify, and solve moral imbecility. These battles over scientific knowledge produced tangible policy consequences. Fear of moral and mental defectives inspired the formation of networks of diagnostic clinics in cities across the country. Diagnostic bureaucracies joined medical experts and members of the public in the common mission of building a better modern America by detecting and disposing of all those society deemed defective. This thesis reveals the significant ways in which moral imbecility’s cultural presence equipped experts with the power to avoid reproach while they, aided by public support and participation, implemented policies of surveillance and institutionalization that held major implications for individual civil liberties